"I don't see many adults on a bicycle" - Is it time to despair for the human race? Reflections on the gap between the numbers of bicycles owned and the numbers of cyclists - Foster, C; Cavill, N (2012)
Objective: This commentary offers a discussion of the paper by Bauman et al. (2011) published in Preventive Medicine. Methods: We discuss the explanations for the findings of the manuscript by Bauman et al. (2011). Results: We argue that there are social, commercial and environmental drivers of cycling rates and agree that there is an urgent need to take action to promote both cycling and build environments to support cycling. Conclusion: The paper by Bauman et al. provides context to help build a better global cycle cultures, involving new partnerships, in a concerted effort to tackle physical inactivity at a worldwide level. © 2011 Elsevier Inc.